INTRINSIC HALAL AWARENESS WITH ISLAMIC BRANDING AS A MODERATION THAT AFFECTS THE ATTITUDE OF THE MUSLIM COMMUNITY TOWARDS HALAL FOOD BRANDS - Nur Sitti Khumairoh; Nur Aida; Nur Qomariah; Ahmad Nasir (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to analyze the influence of intrinsic halal awareness on attitudes toward Islamic branding as a moderation variable. The exogenous variables are intrinsic halal awareness and Islamic branding while attitudes as endogenous variables. The study population was a Muslim community with a total sample of 161 with purpose sampling techniques, namely the study sample was those over the age of 20. The analyzer uses SEM PLS.4. Based on the measurement model, a loading factor value of 0.7, an AVE value of 0.5, and a composite reliability value of 0.7 so that all research indicators were able to contribute strongly to latent variables. Based on the structural model analysis, was obtained of the hypothesis test where Islamic branding has a positive and significant influence on attitudes, intrinsic halal awareness has a positive and significant effect on Islamic branding and intrinsic halal awareness has a positive and significant effect on attitudes. From the test of the influence of moderation, it was found that Islamic branding acts as a partial mediation, meaning that the existence or absence of Islamic branding does not affect the influence of intrinsic halal awareness on the attitude of the Muslim community towards halal food.